Therapeutic Options for the Single Pill Combination of Lisinopril, Amlodipine and Rosuvastatin: a Systematic Review - S. R. Gilyarevsky; M. V. Golshmid; N. G. Bendeliani (Столичная издательская компания, 2022)
Aim. To evaluate the effect of taking a single pill combination of amlodipine, lisinopril and rosuvastatin on blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C) in hypertensive patients with or without severe hypercholesterolemia.Material and methods. Articles published in Russian were selected for analysis. Six articles that met the criteria for inclusion in a systematic review were found by searching the eLibrary database for the keyword "equamer". The results of 5 observational clinical studies were presented in these articles. The effectiveness of the fixed combination of amlodipine, lisinopril and rosuvastatin was assessed mainly by changes in the level of systolic and diastolic blood pressure, the concentration of LDL cholesterol. In addition, the effects of fixed-dose amlodipine, lisinopril, and rosuvastatin on central aortic pressure and its increment index, as well as carotid-femoral pulse wave velocity, were studied in part of the studies. The effect of the fixed combination of amlodipine, lisinopril and rosuvastatin on blood pressure and LDL-C concentration, as well as on these additional indicators, in patients who had a coronavirus infection with severe lung damage was studied in one study.Results. Evidence from a systematic review demonstrates the efficacy of single pill combination amlodipine, lisinopril and rosuvastatin in reducing blood pressure and LDL-C in a wide range of patients with different baseline risk of developing cardiovascular complications and different baseline levels of blood pressure and LDL-C.Conclusion. The data obtained confirm the feasibility of more frequent prescription of the single pill combination of amlodipine, lisinopril and rosuvastatin in clinical practice for the treatment of hypertensive patients with high or moderate risk of developing cardiovascular diseases, including patients with concomitant hypercholesterolemia.